How to Cook a Tapir : a Memoir of Belize. - Fry, Joan (At table series., 2009)
In 1962 Joan Fry was a college sophomore recently married to a dashing anthropologist. Naively consenting to a year-long "working honeymoon" in British Honduras (now Belize), she soon found herself living in a remote Kekchi village deep in the rainforest. Because Fry had no cooking or housekeeping experience, the romance of living in a hut and learning to cook on a makeshift stove quickly faded. Guided by the village women and their children, this twenty-year-old American who had never made more than instant coffee came eventually to love the people and the food that at first had seemed so for